Časopis "Pregled" (1979-1991) / Periodical for Social Issues (1979-1991): Napomene uz Bibliografiju "Pregleda" / Note to Bibliography of Periodical for Social Issues - Dizdar, Senada (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
Note to Bibliography of Periodical for Social Issues.